Winter's orbit - Maxwell, Everina (Tor, a Tom Doherty Associates Book, 2021)
"Summoned before the Emperor, Prince Kiem-a famously disappointing minor royal and the Emperor's least favorite grandchild-is commanded to renew the empire's bonds with its newest vassal planet. The prince must marry Count Jainan, the recent widower of another royal prince of the empire. But the Jainan suspects his late husband's death was no accident. And Prince Kiem discovers that Jainan is a suspect himself. But broken bonds between the empire and its vassal planets leaves the entire empire vulnerable, so together they must prove that their union is strong while uncovering a possible conspiracy. In the shadows of a secret past and an insecure future, Kiem an Jainan must come together to protect both of their worlds."--Provided by publisher.